Adipose-derived mesenchymal stem cell exosomes ameliorate spinal cord injury in rats by activating the Nrf2/HO-1 pathway and regulating microglial polarization - Luo, Yi; He, You-zhi; Wang, Yong-fu; Xu, Yu-xia; Yang, Li (Folia Neuropathologica, 2023)
As of now, there are no satisfactory treatments for spinal cord injury (SCI), so new therapeutic approaches are necessary to be explored. Adipose-derived mesenchymal stem cell exosomes (ADMSC-Exo), delightfully, show remarkable therapeutic effects. Therefore, we try to investigate the effects and mechanisms of ADMSC-Exo on SCI, as well as to provide novel approaches for the treatment of SCI. Adipose-derived mesenchymal stem cells (ADMSC) were isolated from rats and then exosomes (Exo) were extracted from the cells. The extracted Exo were identified by flow cytometry, transmission electron microscopy and nanoparticle tracking analysis (NTA). Then, the SCI rat model was established by the spinal cord impactor and injected with 200 µl PBS or Exo into their tail veins at 30 min, 24 h, and 48 h after surgery. The rats in the Control group and Exo group only exposed the spine. Motor function recovery was assessed on days 0, 7, 14, 21, and 28; histopathological changes and apoptosis levels in spinal cord tissues were observed by HE staining and TUNEL staining; the levels of inflammatory cytokines TNF-a, IL-6, and MCP-1 in spinal cord tissues were measured by ELISA; the expression levels of iNOS, IL-12, Arg1, and Mrc1 in spinal cord tissues were detected by qRT-PCR; and Nrf2, HO-1, and NQO1 protein expression in spinal cord tissues were detected by Western blot. ADMSC-Exo were successfully isolated and identified. ADMSC-Exo significantly relieved SCI and promoted motor function recovery in SCI rats. Moreover, ADMSC-Exo inhibited the expression of both inflammatory factors in the spinal cord tissues and M1 microglia, promoted the expression of M2 microglia, and activated the Nrf2/HO-1 pathway. Altogether, ADMSC-Exo can not only ameliorate SCI, but also promote the motor function recovery of rats. And the mechanism of ADMSC-Exo improving SCI may be achieved by activating Nrf2/HO-1 pathway and microglial polarization.